How Do Nutritional Warnings Work on Commercial Products? Results From a Hypothetical Choice Experiment - de Alcantara, Marcela; Ares, Gastón; Deliza, Rosires (Frontiers in Nutrition, 2022)
A large body of evidence assessing the effectiveness of front-of-package (FOP) nutrition labelling exists. Most experimental studies have been conducted with fictious products. However, consumer’s perception depends on several product extrinsic factors such as brand. Understanding how strong brand associations influence the effectiveness of front-of-package nutrition labelling schemes may be crucial for inform policymaking. In this context, the aim of the present work was to evaluate the effect of five nutritional warnings on consumer choice of commercial products, compared to two FOP nutrition labelling schemes: the guidelines daily amounts (GDA) system and the traffic light system (TLS). An online randomized controlled trial with 1932 participants was used to evaluate the effect of FOP nutrition labelling on participants' willingness to choose the most healthful product in a set of three commercial products, available in the Brazilian marketplace and corresponding to different brands and nutritional composition. Results showed that nutritional warnings and the TLS significantly increased the likelihood of selecting none of the products instead of the least healthful product, or a healthier product, in at least one of the product categories compared to the GDA. In conclusion, warnings tended to encourage the category abandonment and within-category product substitution which suggests that they could contribute to healthier food choices.